POLISH POPULISM AND THE COUNCIL OF EUROPE: HOW POLAND IS FAILING TO ADHERE TO ITS CORE OBLIGATIONS AND WHAT IT MEANS (Georgian Journal for European Studies, 2022)
This paper explores the relationship between the Polish state and the Council of Europe  (CoE). It examines the actions of the Law and Justice party and how such  actions have affected the country’s relationship to the CoE, with particular reference to its three core values: Human Rights, Democracy, and the Rule  of Law. It will determine that as a consequence of recent policies and laws the state is no longer adhering to its obligations.